Relearning emotional skills: a proposal for educators - Romero Llanos, Katerine (2024)
Numerous studies have demonstrated that teachers constitute a professional group with a higher vulnerability to developing emotional exhaustion, burnout, and chronic stress, it becomes imperative to address the need for learning and relearning emotional skills among educators, both during their training and during of their professional activities. In order to address this inadequately understood and addressed need, based on the conceptual and methodological framework developed by Mayer and Salovey, the Program “Relearning to Learn About My Emotions” has been created for Regular Basic Education teachers. This program will consist of 10 sessions, each lasting 60 minutes. These sessions will include moments of theoretical information, individual and group activities, sharing of experiences, and, above all, the suggestion of practicing the emotional skill under study throughout the week until the next session, where the personal experience of each trained skill will beencouraged. Technical instruments will be administered at the beginning and conclusion of the program to assessthe initial and final states. A reinforcement session will be conducted after two months. This proposal is submittedfor consideration to the authorities responsible for designing and implementing educational policies and to theacademic community at large.